Designer's attributes in refurbishment projects: case study in Malaysia - Ali, A.S.; Alias, A. (2010)
for refurbishment works featuring in the ninth Malaysia Plan and the resultant high demand for refurbishment works. Refurbishment works are mainly contributed to by an increase in the number of building renovation projects, extensions and projects featuring extensive repair works, However, refurbishment designs are difficult to manage compared to new-build projects. In refurbishment design, the individual ues~gneris the one who ultimately determines the quality and performance of a project, not his or her o~ganization. Hence, various specific attributes are essentiel 10 designers undertaking refurbishment projects; these directly influence the refurbishment project's performance. The Illam objectives of this paper are to identify these important attributes in designers of refurbishment works and to show how they affect overall Performance of projects. 'This study employed quantitative approaches to data collection. The study started with the identification of important designer attributes through literature reviews followed by a questionnaire survey. A set of questionnaire was distributed to 100 selected designers of refurbishment projects in Malaysia. Descriptive and inferential statistics are used in the data analysis. In conclusion, the study identified six key attributes for designers in refurbishment projects. The associative test shows that to improve performance of refurbishment Projects:the designers need to have knowledge, enthusiasm, commiunent and coordination skills